2006
DOI: 10.1364/ao.45.001062
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo-based inverse model for calculating tissue optical properties Part I: Theory and validation on synthetic phantoms

Abstract: A flexible and fast Monte Carlo-based model of diffuse reflectance has been developed for the extraction of the absorption and scattering properties of turbid media, such as human tissues. This method is valid for a wide range of optical properties and is easily adaptable to existing probe geometries, provided a single phantom calibration measurement is made. A condensed Monte Carlo method was used to speed up the forward simulations. This model was validated by use of two sets of liquid-tissue phantoms contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
342
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 311 publications
(345 citation statements)
references
References 20 publications
1
342
0
2
Order By: Relevance
“…Details about the Monte-Carlo-based inverse model of diffuse reflectance can be found in previous publications. 17,18,27 The accuracy of the inverse model was verified using experimental tissue phantom studies. The results indicated that for phantoms with a wide range of absorption coefficients (0 to 20 cm −1 ) and reduced scattering coefficients (7 to 33 cm −1 ), optical properties could be extracted within an average error of 3% for phantoms containing hemoglobin and within 12% for phantoms containing nigrosin.…”
Section: Extraction Of Tissue Optical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Details about the Monte-Carlo-based inverse model of diffuse reflectance can be found in previous publications. 17,18,27 The accuracy of the inverse model was verified using experimental tissue phantom studies. The results indicated that for phantoms with a wide range of absorption coefficients (0 to 20 cm −1 ) and reduced scattering coefficients (7 to 33 cm −1 ), optical properties could be extracted within an average error of 3% for phantoms containing hemoglobin and within 12% for phantoms containing nigrosin.…”
Section: Extraction Of Tissue Optical Propertiesmentioning
confidence: 99%
“…The results indicated that for phantoms with a wide range of absorption coefficients (0 to 20 cm −1 ) and reduced scattering coefficients (7 to 33 cm −1 ), optical properties could be extracted within an average error of 3% for phantoms containing hemoglobin and within 12% for phantoms containing nigrosin. 27 The diffuse reflectance spectra were fit to the Monte Carlo model in the wavelength range of 350 to 600 nm. The primary intrinsic absorbers in the model over this wavelength range were assumed to be oxygenated and deoxygenated hemoglobin and beta-carotene.…”
Section: Extraction Of Tissue Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, spectra were corrected for daily variations in optical throughput using a Spectralon reflectance standard, and were normalized by the CCD integration time. An inverse Monte Carlo model [11,15,16] was used to obtain values for THb concentration, β-carotene concentration and the wavelength-averaged reduced scattering coefficient from 450-600 nm (<µ s '>), for each measured site (or pixel) on the specimen surface. Upon completion of the measurements, the measured sites were inked for histological correlation.…”
Section: Methodsmentioning
confidence: 99%
“…Since each of the absorption spectra are known, the only assumption necessary to make about the tissue is the form of wavelength-dependent scattering. To date, we have assumed that scatterers in tissue can be modeled as spherical particles of a single size using Mie theory [11,15,16]. Clearly, however, cellular scatterers are neither spherical, nor of a single size.…”
Section: Impact Of Scattering Model On Extracted Optical Propertiesmentioning
confidence: 99%